2015
DOI: 10.1128/mbio.01777-15
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational Modification of HOIP Blocks Toll-Like Receptor 4-Mediated Linear-Ubiquitin-Chain Formation

Abstract: Linear ubiquitination is an atypical posttranslational modification catalyzed by the linear-ubiquitin-chain assembly complex (LUBAC), containing HOIP, HOIL-1L, and Sharpin. LUBAC facilitates NF-κB activation and inflammation upon receptor stimulation by ligating linear ubiquitin chains to critical signaling molecules. Indeed, linear-ubiquitination-dependent signaling is essential to prevent pyogenic bacterial infections that can lead to death. While linear ubiquitination is essential for intracellular receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…This protein has previously been shown to be an important part of the coral immune response in multiple studies and has been linked to host production of antimicrobial compounds [ 47 , 48 ]. Other TLR-related contigs we observed to be differentially expressed included tumour necrosis factor receptor-associated factor 6 [ 49 , 50 ], and contigs involved in the negative regulation of TLR signalling, E3 ubiquitin-protein ligase RNF31 [ 51 ] and 4 copies of ubiquitin carboxyl-terminal hydrolase CYLD [ 52 ]. Additionally, we observed upregulation of the protein argonaute 2, an antiviral protein that has previously been described as part of the response of acroporid corals to white diseases [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This protein has previously been shown to be an important part of the coral immune response in multiple studies and has been linked to host production of antimicrobial compounds [ 47 , 48 ]. Other TLR-related contigs we observed to be differentially expressed included tumour necrosis factor receptor-associated factor 6 [ 49 , 50 ], and contigs involved in the negative regulation of TLR signalling, E3 ubiquitin-protein ligase RNF31 [ 51 ] and 4 copies of ubiquitin carboxyl-terminal hydrolase CYLD [ 52 ]. Additionally, we observed upregulation of the protein argonaute 2, an antiviral protein that has previously been described as part of the response of acroporid corals to white diseases [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, E3 RNF125 induces degradation of RIG-I, MDA5, and MAVS [ 30 , 31 ]. E3 enzymes HOIL-1 L and HOIP mediate linear ubiquitination, in which the C-terminal carboxyl groups of ubiquitin is conjugated to the α-amino group of N-terminus of another ubiquitin, inhibit RIG-I signaling [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bowman and colleagues showed that, when nondegradative ubiquitin chains are attached to Lys1056, a conformational change is triggered that inhibits the ligase activity of HOIP. Conversely, a single amino acid substitution at this location (K1056R) prevents ubiquitination and results in a constitutively active LUBAC and corresponds to increased abundance of linear chains in resting and LPS-stimulated B cells (63). Together, these studies highlight the diverse pathways engaged in maintaining tight control over NF-kB activation downstream of LUBAC.…”
Section: Physiological Roles Of Linear Ubiquitin Chainsmentioning
confidence: 94%